2nd International Multidisciplinary Microscopy and Microanalysis Congress Proceedings of InterM, October 16-19, 2014 - Polychroniadis, E.K.; Polychroniadis, E.K.; Oral, Ahmet Yavuz.; Oral, Ahmet Yavuz.; Ozer, Mehmet.; Ozer, Mehmet. (Springer Proceedings in Physics, 2015)
The 2nd International Multidisciplinary Microscopy and Microanalysis Congress & Exhibition (InterM 2014) was held on 16–19 October 2014 in Oludeniz, Fethiye/ Mugla, Turkey. The aim of the congress was to gather scientists from various branches and discuss the latest improvements in the field of microscopy. The focus of the congress has been widened in an "interdisciplinary" manner, so as to allow all scientists working on several related subjects to participate and present their work. These proceedings include 33 peer-reviewed technical papers, submitted by leading academic and research institutions from over 17 countries and representing some of the most cutting-edge research available. The papers were presented at the congress in the following sessions: ·         Applications of Microscopy in the Physical Sciences ·         Applications of Microscopy in the Biological Sciences.